RANCANGAN SISITEM PENGENDALIAN PPROSES POLIMERISASI FENOL FORMALDEHIDA (Design of Process Control System for Phenol Formaldehyde Plimerization) - Hermawan Thaheer (KOMPUTASI, 2009)
Penol Formaldehyde Polymer production in indonesia mostly used the batch systemThat have high risk technologies. Naturally , the condesation process Beetween phenol and fomaldeled are exothermic that realse about 315.77 Mcal of 5 ton production and the reactor temperature may condition. Process control system using manual units are : i) steam supply ; and 2)Cooling water supply; Both of control unit be operated .all of analofg display must be convering to digital indefendent all. After the computer processing the data. Result is informed to reactor for apparants control action. Keywords : Phenol Formaldhyde Polymer: Process Control: Automation